Determinants of online shopping intention - Nik Mat, Nik Kamariah; Meor Ahmad, Siti Salwani (2005)
The internet has become a key medium for the purchase of products and services in virtual markets and has effectively linked all countries and business. It has been estimated that the internet market is worth $300 billion in 1995. Through the internet, electronic commerce offers a tremendously wide variety of electronic business opportunities. One of them is online shopping which has become the third most popular internet activity after e-mail or instant messaging and web browsing. Malaysia is ranked 17th among 27 countries across Europe, Asia-Pacific and North America in terms of the percentage of internet users shopping online. Even though this method has started to win hearts of Malaysian consumers, the factors influencing the willingness to shop online are still unknown. Thus, the general objective of the study is to examine the factors that influence consumer's online shopping intention (dependent variable). The main independent variables are demographic, trusts, quality and loyalty to website visited. A 100 percent response rate was obtained from students sampled randomly. Findings indicate that quality and loyalty contributed 26.8 percent (R2 = 0.268) and 6.1 percent (R2 = 0.061) respectively to the variance in online shopping intention. Implications of the study are discussed.